Tone features, tone perception, and peak alignment in Thai. - Zsiga E; Nitisaroj R (Language & Speech, 2007)
This paper investigates the relationship between the phonological features of tone and tone perception in Thai. Specifically, it tests the hypothesis (proposed by Morén & Zsiga, 2006) that the principle perceptual cues to the five-way tonal contrast in Thai are high and low pitch targets aligned to moras. Results of four perception studies, one using natural speech and three using digitally-altered speech, are presented in support of the hypothesis. It is argued that, by associating tones to moras, a straightforward mapping from the abstract autosegmental features H and L to the production and perception of Thai tones, a heretofore elusive goal, can be accomplished. This result has consequences for theories of contour tone perception, the distinctive features of tone, and the alignment of pitch targets to the segmental string.